1993
DOI: 10.1192/bjp.162.1.93
|View full text |Cite
|
Sign up to set email alerts
|

The Community's Tolerance of the Mentally Ill

Abstract: A survey of attitudes to mental illness was conducted in a quota sample of about 2000 subjects in Malvern and Bromsgrove. Factor analysis showed three main components - benevolence, authoritarianism, and fear of the mentally ill. Residents of Bromsgrove, which is served by a traditional mental hospital, were slightly more tolerant than those living in Malvern, which has a community-based service, and has seen the closure of two mental hospitals in its vicinity during the last 10 years. The main demographic det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
255
4
21

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(305 citation statements)
references
References 0 publications
25
255
4
21
Order By: Relevance
“…Research participants who reported greater pity for people with mental illness endorsed more mandated treatment. This is consistent with authoritarian notions about people with mental illness (Brockington, Hall, Levings, & Murphy, 1993;Taylor & Dear, 1980). Namely, the mental health system should mandate some services for people with mental illness because of parental concern.…”
Section: Discussionsupporting
confidence: 51%
“…Research participants who reported greater pity for people with mental illness endorsed more mandated treatment. This is consistent with authoritarian notions about people with mental illness (Brockington, Hall, Levings, & Murphy, 1993;Taylor & Dear, 1980). Namely, the mental health system should mandate some services for people with mental illness because of parental concern.…”
Section: Discussionsupporting
confidence: 51%
“…Research has shown that an advanced understanding of an illness imbues positive attitudes towards it (Brockington et al, 1993), and with schizophrenia this can perhaps be achieved by making people aware of the facts regarding its known pathophysiology and successful management. This is best achieved in adolescence, when individuals are at their most receptive and are themselves dealing with similar issues regarding their identity and psychological well-being.…”
Section: Schizophrenia … By Any Other Name?mentioning
confidence: 99%
“…Contact is added to education in order to facilitate a more accurate view of stigmatized groups. Among those, education and contact-based education have been found to reduce stigmatizing attitudes (e.g., Brockington, Hall, Levings, & Murphy, 1993;Corrigan et al, 2001;Corrigan et al, 2002;Link, Cullen, Frank, & Wozniak, 1987;Morrison, 1980;Penn et al, 1994).…”
Section: Mental Health Stigma and Stigma Reduction Interventionsmentioning
confidence: 99%